Analisis Reaksi Pasar dan Risiko Investasi antara Perusahaan Perata Laba dan Buka Perata Laba - Brahm Ardhi Noviant; Marsono Marsono (Jurnal Akuntansi dan Auditing, 2013)
The research aims to: 1) Analyzing is there any difference of market reaction between income smoothers and non income smoothers companies. 2) Analyzing is there any difference of investment risk between the income smoothers and non income smoothers companies. The research was done to manufactures companies listed in BEI. Among 149 manufactures companies listed in BEI, 48 companies were taken to become sample. Using Eckel Index, the sample were divided into two type, 9 income smoothers and 39 non income smoothers. Documentation technique was used to gather data. Independent sample t-test was used to analyzed data if it has normal distribution in Kolmogorov-Smirnov test. The result show that there was no difference of the market reaction between income smoothers and non income smoothers companies, and there was no difference of investment risk between income smoothers and non income smoothers companies. It’s because the result of independent sample t-test show the probability of amount market reaction and investment risk were not significant in 5%.